Technology roadmapping based On patent citation network considering technology life cycle - Yujin Jeong; Byungun Yoon (2011 IEEE International Technology Management Conference, 2011)
Although there have been many studies conducted that deal with technology roadmap structure or roadmapping methods, most existing approaches concentrate on market-driven roadmapping. Moreover, a lot of the research depends on qualitative analysis; thus, less rigorous research has been conducted through quantitative analysis or systematic approaches. Hence, this paper aims to propose a new technology roadmapping approach considering technology life cycle through patent citation analysis, which is a relatively robust method of quantitative analysis. At first, patent data of relevant technologies and citation information are collected. Using these data, a patent citation network that consists of nodes (individual patents) and arcs between nodes (citation links between patents) is developed. Secondly, a stage of a selected technology in the life cycle is investigated by considering the year of patent application and the life cycle of the technology. Thus, the lifetime of a technology is estimated to plan the duration of technology development. In addition, subsequent technologies are grouped as nodes of a super-level technology to show the evolution of the technology for the period. Finally, a technology roadmap is drawn by connecting these technology nodes in a technology layer and estimating the duration of development time. In this paper, solar energy-related technology is chosen in order to illustrate the process of the proposed method. The results of this paper can be regarded as a novel approach to technology-driven roadmapping that effectively utilizes the quantitative patent data.